Upaya Meningkatkan Keterampilan Membaca Melalui Metode Global Di Kelas 2 Sekolah Dasar Negeri 117830 - Cici Rahayu; Devi Amanda; Sakinah Aulia (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Reading skills are very important for elementary school students to master. To improve reading skills in elementary school is to use global methods. This research aims to determine the beginning reading ability of grade 2 students in elementary school. Based on the author's initial observations of the initial reading skills of grade 2 students at State Elementary School (SDN) 117830, low results were obtained. This can be seen from the symptoms that occur in learning, such as students being less active, not understanding letters, not understanding punctuation marks and students' low reading skills. This research is classroom action research. It consists of several main aspects of treatment and observation, namely increasing initial reading skills using global methods which were implemented at SDN 117830, involving 28 students consisting of 15 girls and 13 boys who were registered in the 2023/2024 academic year, using a research design Kemmis and Mc. Taggart which consists of two cycles. Each cycle is held twice in class and each cycle consists of four stages, namely planning, implementation, observation and reflection. The results of the research showed that in the first cycle of action, the average ability of students to read at the beginning reached 66% and the ability of students to read classically was 54%. In the second cycle of action, there was an increase in the initial reading ability to reach 87%, while the classical reading ability was 93%. Thus, it can be concluded that the application of the global method can improve the beginning reading skills of grade 2 students at SDN 117830.